Stroke frequency and arm coordination in front crawl swimming - Potdevin, F.; Bril, B.; Sidney, M.; Pelayo, P. (International Journal of Sports Medicine, 2006)
This study aims to determine whether the arm coordination observed at different stroke rates (SR, number of arm stroke cycles per minute) differs according to the level of expertise. Thirteen non-expert (GNE) and 14 expert (GE) swimmers swam crawl five 25-m lengths at five stroke rate values: 35, 40, 45, 50, and 55 cycles · min-1. Results show that the pattern of 45 % of GNE switched from the catch-up (a lag time is performed between the propulsive phases of the two arms) to the superposition coordination mode (both arms pushing simultaneously during a short period of the cycle) between 45 and 50 cycles · min-1. Patterns of 62.4 % of GE switched in the same way between 50 and 55 cycles · min-1. Significant differences in coordination patterns were found between GNE and GE only when SR was set at 45 cycles · min-1. As non-expert swimmers seldom produce the superposition mode, but adopt this pattern when required to swim at high stroke rate values, it is suggested that this coordination mode is an emergent property of the movement.